KESALAHAN PENGGUNAAN AWALAN DI- DAN KE- DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS I SEKOLAH DASAR - Sukmaratri, Wiganingtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the errors in the use of the prefixes di- and ke- that are often made by grade I Elementary School (SD) students in learning Indonesian. Mastery of these prefixes is important in the formation of passive verbs (di-) and direction or place indicators (ke-). This qualitative descriptive study analyzed the work documents of 40 grade I students from four elementary schools in the Ki Hajar Dewantoro Cluster, Wonogiri. The results of the study showed several types of errors, including the inability to distinguish di- as a prefix and preposition, as well as confusion in the use of di- and ke- as prepositions. Mistakes in the use of di- in active verbs and inappropriate use of ke- were also found. These errors are caused by students' lack of understanding of the function of prefixes and prepositions. The implication of this study is the need for a more contextual and effective learning strategy to improve the understanding and mastery of the prefixes di- and ke- in grade I elementary school students.